Ecclesial exegesis: a synthesis of ancient and modern approaches to scripture - Vall, Gregory (Verbum domini, 2022)
"Biblical scholarship informed by the faith of the Church and to serve the life of the Church is called ecclesial. In 1988, Joseph Ratzinger put forward a proposal of what this should mean, which he called "Method C," in contrast to the patristic-medieval approach (Method A) and the historical-critical approach (Method B). This book examines the warrant for the Method C proposal in the document Dei Verbum of the Second Vatican Council, and offers nine studies applying this method that bring to the surface issues such as the relationship between Old Testament and New Testament, literal sense and spiritual sense, and Scripture and Tradition"--